Ovarian responses and conception rates in response to GnRH, hCG, and progesterone - M.A. Portaluppi; D.E. Tenhouse; A. Lloyd; D.R. Eborn (Kansas Agricultural Experiment Station Research Reports, 2006)
We hypothesized that increasing concentrations of progesterone after artificial insemination (AI) would increase fertility. Our objective was to assess changes in ovarian structures, incidence of ovulation, and change in serum progesterone in response to GnRH, human chorionic gonadotropin (hCG), or exogenous progesterone (controlled internal drug release; CIDR insert) treatment, beginning 4 to 9 days after AI (d 0) and again 7 days later (Exp. 1). Blood was collected from 753 cows in 3 herds on days 0 and 7. Ovaries of 162 cows in 1 herd were scanned and mapped to confirm the presence a corpus luteum (CL), and cows were assigned randomly to serve as control (n = 41) or to receive a CIDR insert for 7 days (n = 41), 100 Î¼g of GnRH (n = 40), or 3,300 IU of hCG (n = 40). More cows were induced to ovulate in response to GnRH (60%) and hCG (78%), compared with control (2.4%). Compared with control, cows treated with GnRH or hCG had more induced CL (d 7) and more total CL (d 7), but serum progesterone was increased only in response to hCG. Volume of the original luteal structures was increased by hCG, but tended to be reduced by CIDR and GnRH, compared with luteal volume in control. Total CL volume was increased by hCG, but reduced by CIDR, compared with CL volume of control. In Exp. 2, cows in 5 herds were used to assess conception rates in response to the same treatments described in Exp. 1: control (n = 708), CIDR (n = 711), GnRH (n = 719), and hCG (n = 714). Tendencies for interactions of treatment x herd and treatment x lactation group were detected, but no 3-way interactions were found. Treatment with hCG increased conception rates in second-lactation cows. The CIDR tended to increase, and hCG increased, conception rates in 2 herds, whereas the CIDR decreased conception rates in 1 herd. We concluded that GnRH and hCG effectively induced ovulation, and increased number of CL, but only hCG increased serum progesterone. Further, treatment with the CIDR or hCG increased conception rates, but only in some herds.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; CIDR; GnRH; hCG; Pregnancy rate